2012
DOI: 10.1177/030089161209800211
|View full text |Cite
|
Sign up to set email alerts
|

CK19, CK20, EGFR and HER2 Status of Circulating Tumor Cells in Patients with Breast Cancer

Abstract: The results suggest that the investigation of CK20 mRNA with other biomarkers in the peripheral blood of breast cancer patients may be useful to monitor the presence of disseminated tumor cells in the blood circulation and to predict the prognosis of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…As fibrous tissue proteins distributed in epithelial cells, the CK protein family participates in the formation of the cytoskeleton and in regulation of cell differentiation and movement (Tunca et al, 2012). Recently, the CK20 protein has received increased interest due to its highly specific expression in both colorectal and gastric cancers (Kim et al, 2009;Sun et al, 2012;Kim et al, 2013;Tunca et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As fibrous tissue proteins distributed in epithelial cells, the CK protein family participates in the formation of the cytoskeleton and in regulation of cell differentiation and movement (Tunca et al, 2012). Recently, the CK20 protein has received increased interest due to its highly specific expression in both colorectal and gastric cancers (Kim et al, 2009;Sun et al, 2012;Kim et al, 2013;Tunca et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that C20 positivity was more frequent in BC patients with aggressive tumors compared to other BC patients. On the other hand, mRNA expression of CK19, EGFR and HER2 was not significantly associated with the clinical and pathological characteristics of BC patients [6]. Although our previous findings indicate a potential relationship between these CTMs and aggressive tumor characteristics in BC, two facets related to the clinical utility of CTMs remained unaddressed as follows: 1) the predictive ability of CTMs for both local recurrence and distant metastasis and 2) the effect of therapy on CTM ability to predict distant metastasis.…”
Section: Introductionmentioning
confidence: 56%
“…In a previous study [6], we analyzed the prognostic importance of the circulating tumor markers (CTMs) cytokeratin 19 (CK19), CK20, epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) in BC. We showed that C20 positivity was more frequent in BC patients with aggressive tumors compared to other BC patients.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to concentrate on the following genes: Cytokeratin 19, which is also used in the immunohistochemical detection of cancer cells (APAAP-staining) (21,22) and is a marker for shorter disease free survival and reduced overall survival in breast cancer patients (23)(24)(25)(26). Furthermore it is especially expressed in metastatic breast cancer cells (27,28) and was already used as a biomarker for CTCs in the blood of breast cancer patients (29). Furthermore CK19 was shown to be expressed in CTCs from early and metastatic breast cancer patients, together with the EMT-markers Twist and Vimentin (30), so it could be concluded, that this epithelial marker is not downregulated by EMT.…”
Section: Introductionmentioning
confidence: 99%